In vitro digestion and fermentation characteristics of canola co-products simulate their digestion in the pig intestine. (24th November 2015) - Woyengo, T. A.; Jha, R.; Beltranena, E.; Zijlstra, R. T.
Abstract : Canola co-products are sources of amino acid and energy in pig feeds, but their fermentation characteristics in the pig intestine are unknown. Thus, we determined the in vitro fermentation characteristics of the canola co-products Brassica juncea solvent-extracted canola meal (JSECM), Brassica napus solvent-extracted canola meal (NSECM), B. napus expeller-pressed canola meal (NEPCM) and B. napus cold-pressed canola cake (NCPCC) in comparison with soybean meal (SBM). Samples were hydrolysed in two steps using pepsin and pancreatin. Subsequently, residues were incubated in a buffer solution with fresh pig faeces as inocula for 72 h to measure gas production. Concentration of volatile fatty acids (VFA) per gram of dry matter (DM) of feedstuff was measured in fermented solutions. Apparent ileal digestibility (AID) and apparent hindgut fermentation (AHF) of gross energy (GE) for feedstuffs were obtained from pigs fed the same feedstuffs. On DM basis, SBM, JSECM, NSECM, NEPCM and NCPCC contained 15, 19, 22, 117 and 231 g/kg ether extract; and 85, 223, 306, 208 and 176 g/kg NDF, respectively. In vitro digestibility of DM (IVDDM) of SBM (82.3%) was greater ( P< 0.05) than that of JSECM (68.5%), NSECM (63.4%), NEPCM (67.5%) or NCPCC (69.8%). The JSECM had greater ( P< 0.05) IVDDM than NSECM. The IVDDM for NSECM was lower ( P< 0.05) than that for NEPCM, which was lower ( P< 0.05) than that for NCPCC. Similarly, AID of GE was greatest for SBM followed by NCPCC, JSECM, NEPCM and then NSECM. Total VFA production for SBM (0.73 mmol/g) was lower ( P <0.05) than that of JSECM (1.38 mmol/g) or NSECM (1.05 mmol/g), but not different from that of NEPCM (0.80 mmol/g) and NCPCC (0.62 mmol/g). Total VFA production of JSECM was greater ( P <0.05) than that of NSECM. Total VFA production of NSECM was greater ( P <0.05) than that of NEPCM or NCPCC, which differed ( P <0.05). The ranking of feedstuffs for total VFA production was similar to AHF of GE. In conclusion, in vitro fermentation characteristics of canola co-products and SBM simulated their fermentation in the small and large intestine of pigs, respectively. The 30% greater VFA production for JSECM than NSECM due to lower lignified fibre of JSECM indicates that fermentation characteristics differ between canola species. The NSECM had the highest fermentability followed by NEPCM and then NCPCC, indicating that fat in canola co-products can limit their fermentability in the hindgut.